ChemInform Abstract: An Imidazoline—Aminophenol (IAP) Nickel Catalyst: Structure and Catalytic Activity in the Enantioselective 1, 4‐Addition of 3′‐Indolyl‐3‐oxindoles to Nitroethylene. Issue 35 (2nd September 2014) - Awata, Atsuko; Wasai, Makiko; Masu, Hyuma; Kado, Sayaka; Arai, Takayoshi
Abstract The title catalyst is successfully applied in asymmetric 1, 4‐addition of 3′‐indolyl‐3‐oxidole to nitroethylene.